Oral Cancer Frequency at Different Sub Sites of Oral Cavity: A Study from Tertiary Care Hospital of Karachi, Pakistan - Siddiqui, Imtiaz Ather; Khan, Hurtamina; Siddiqui, Riaz; Hafeez, Mahum; Dogar, Muhammad Razzak; Shahid, Wajeeha; Qureshi, Sameer (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
Introduction: Carcinoma of oral cavity is amongst the first ten commonest malignancies in Pakistan. Oral squamous cell carcinoma is the most common intra oral site manifesting as a chronic, indurated ulcer. Oral cavity sub sites include lips, gum, floor of mouth, mucosa of cheeks, vestibule, anterior two third of tongue, retro molar trigone, hard and soft palate and uvula these sub sites show a variation of trend, onset of cancer. Causes are Aerica nut, tobacco and low consumption of alcohol in our society as compared to developed part of the globe. Objective: The primary objective of the study is to determine the frequency of oral cancer in sub sites of oral cavity. Subject and Methods: This was a cross sectional study that took place in Ear nose throat, Head and Neck surgery Department, Jinnah Postgraduate Medical Centre Jinnah Sind Medical University Karachi, for four years, from 1st January 2013 to 1st January 2016. A total of 105 patients having chronic oral ulcer of three months or more duration, growth in oral cavity, either gender reporting for treatment at ENT JPMC OPD were registered for the study. Detail like sub site oral lesion, technique of sampling like punch biopsy to be done by expression biopsy and Histopathological reports were entered. Results: Squamous cell carcinoma is the predominant type of oral cancer and tongue is the commonest site of origin for these cancers. The average age of the patients was 48.52 ± 5.24 years. There were 61% male and 39% were female. The commonest sites involved were cheek mucosa, lips, tongue, gum with (36.2%), (25.7%), (20%), (18%) respectively. Conclusion: Cheek mucosa is the commonest site of oral cancer with middle age group and male predominance. These results are similar to previous studies with acceptable differences in proportions and common sites involved. However, most of the studies have shown male predominance and middle to old age involvement. Based on these findings, inferences, strength, and limitations, it is recommended to organize further epidemiological studies with large sample, multiple settings and objectives to reach a firm conclusion.